A NON-FATAL ATTACK BY THE TIGER SHARK, Galeocerdo cuvieri, ON THE NORTHEAST COAST OF BRAZIL (CHONDRICHTHYES:CARCHARHINIDAE) - Gadig, Otto Bismarck Fazzano; Sazima, Ivan (Arquivos de Ciências do Mar, 2017)
This paper presents a description of a non-fatal attack by the tiger shark, Galeocerdo cuvieri, whose identification based on a tooth fragment removed from the victim’s wounds. He was a 25-year-old surfer attacked on March 1, 1994, at Boa Viagem Beach, Recife, Northeastearn Brazil, suffering lesions in the left leg, caused by, at least, one biting. A tooth fragment measuring about 2.5 mm was surgically removed from the upper portion of the fibula. According to a more careful analysis, this fragment seems to be from the comissural margin of the third to fifth right upper tooth of that species. The estimated size of the attacking tiger shark was about 2.0-2.5 m TL, judging from the comparative analysis of the tooth fragment, the size and position of the wounds, and the victim’s description.